Activated translation signaling in placenta from pregnant women with gestational diabetes mellitus: possible role of leptin - Pérez Pérez, A. (2013)
Placentas from gestational diabetes (GDM) suff er from structural and functional changes including overgrowth. That is why we aimed to study [ 3 H]-leucine incorporation into protein in addition to translation signaling in placenta from GDM. Thus, we investigated the expression of leptin and leptin receptor (LEPR), as well as the activation state of signaling proteins regulating protein synthesis, such as mTOR, S6 Kinase, EIF4E-BP1, EIF4E, and eEF2 by measuring protein phosphorylation by immunoblot. [ 3 H]-Leucine incorporation into protein also was determined in trophoblastic placenta explants from GDM and control pregnancy. We found that leptin and LEPR expression are increased in placentas from GDM and the translation machinery activity as well as [ 3 H]-leucine incorporation into protein were higher in placentas from GDM compared with placentas from control pregnancy. In conclusion, protein synthesis rate is increased in placenta from GDM patients, and this may be due, at least in part, by the activation of translation signaling. The increased expression of leptin and LEPR may contribute to these eff ects. These results may provide a possible mechanism for the previously observed increase in placenta growth in GDM.